THE EFFECT OF INVESTOR SENTIMENT MANAGER BEHAVIOR AND INVESTMENT OPPORTUNITY SET (IOS) ON COMPANY VALUE WITH DIVIDEND POLICY AS INTERVENING VARIABLES - Nurwulandari, Andini; M. Oktavianta Nurlaya Djaya (Jurnal Ekonomi, 2022)
This study was conducted to examine the effect of investor sentiment, manager behavior, and investment opportunity set (IOS) using the Market Turnover (MTO) proxy, Debt to Equity Ratio (DER), Market Value to Book Value of Equity (MVEBVE) on firm value through policy dividends on LQ45 Index Issuers for the 2016-2020 period. The sample of this study used purposive sampling method with 100 samples of data from 20 LQ 45 index issuers listed on the Indonesia Stock Exchange. The dependent, independent, and intervening variables were measured by a ratio scale. This research uses a quantitative approach with Partial Least Square analysis technique from the SmartPLS program. The results of this study indicate that the independent variables, namely investor sentiment (MTO) and manager behavior (DER) have no significant effect on firm value, while the IOS variable (MVEBVE) has a significant effect on firm value